Change in the electrical conductivity of SnO2 crystal from n-type to p-type conductivity - Villamagua Conza, L. (2015)
The long-sought fully transparent technology will not come true if the n region of the p-n junction does not get as well developed as its p counterpart. Both experimental and theoretical efforts have to be used to study and discover phenomena occurring at the microscopic level in SnO2 systems. In the present paper, using the DFT + U approach as a main tool and the Vienna ab initio Simulation Package (VASP) we reproduce both intrinsic n-type as well as p-type conductivity in concordance to results observed in real samples of SnO2 material. Initially, an oxygen vacancy (1.56 mol% concentration) combined with a tin-interstitial (1.56 mol% concentration) scheme was used to achieve the n-type electrical conductivity. Later, to attain the p-type conductivity, crystal already possessing n-type conductivity, was codoped with nitrogen (1.56 mol% concentration) and aluminium (12.48 mol% concentration) impurities. Detailed explanation of structural changes endured by the geometry of the crystal as well as the changes in its electrical properties has been obtained. Our experimental data to a very good extent matches with the results found in the DFT + U modelling. (C) 2015 Elsevier B.V. All rights reserved.